Radiation Induced Decoloration of Reactive Dye in PVA Films for Film Dosimetry - Shaheen Akhtar; Taqmeem Hussain; Aamir Shahzad; Qamar-ul-Islam; Muhammad Yousuf Hussain; Nasim Akhtar (Journal of Basic & Applied Sciences, 2021)
The investigation of film dosimeters made from polyvinyl alcohol (PVA) films dyed with methyl orange (MO) to enable their use in high dose radiation processing applications was studied. The dosimetric change in these films at pre and post irradiation was studied spectrophotometrically. Radiolytic bleaching was observed in PVA aided films exposed with Cs137 γ-source in dose range of 100-200kGy. The effects of pH, dye concentration and film thickness on the radiation response of the film dosimeters were discussed. The stability of MO-PVA films before and after exposure of radiation was also examined at ambient temperature and was found to be higher for long times at pre and post irradiation stages.